2020
DOI: 10.3390/ijerph17124391
|View full text |Cite
|
Sign up to set email alerts
|

Human Breathable Air in a Mediterranean Forest: Characterization of Monoterpene Concentrations under the Canopy

Abstract: Monoterpenes have been identified as potential determinants of the human health effects induced by forest exposure. The present study characterizes the total monoterpene concentrations at nose height in a Mediterranean Holm oak forest located in North-East Iberian Peninsula during the annual emission peak (summer and autumn: June to November) using a Proton Transfer Reaction–Mass Spectrometry (PTR-MS). Results show a strong variability of the total monoterpene concentrations in season and daytime. The concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 51 publications
7
20
0
Order By: Relevance
“…The biochemical composition of forest air tends to follow diurnal variations, with BVOCs concentration usually peaking early in the afternoon and, especially in summertime, even in the morning (around 2 h after dawn), and it can be markedly influenced by several factors, including meteorological conditions, altitude, seasons, sunlight exposure, and tree types [ 31 , 32 ]. For example, it has been demonstrated that the air of forests dominated by conifer trees has a higher concentration of VOCs if compared to that of forests with more deciduous trees [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The biochemical composition of forest air tends to follow diurnal variations, with BVOCs concentration usually peaking early in the afternoon and, especially in summertime, even in the morning (around 2 h after dawn), and it can be markedly influenced by several factors, including meteorological conditions, altitude, seasons, sunlight exposure, and tree types [ 31 , 32 ]. For example, it has been demonstrated that the air of forests dominated by conifer trees has a higher concentration of VOCs if compared to that of forests with more deciduous trees [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…From a quantitative point of view, studies which aimed to determine the atmospheric concentration of some categories of BVOCs under forest canopy reported heterogeneous findings, probably due to a significant influence of the abovementioned factors on the forest air composition: approximately, on the basis of available evidence, the total amount of terpenes can vary from a minimum of 3.5 to a maximum of 56.0 μg/m 3 , isoprene can range from 0.1 to 28.0 μg/m 3 , and monoterpenes may have an average concentration of 4.5 μg/m 3 , whereas the amount of LOX pathway products is usually below the upper threshold of 3.4 μg/m 3 [ 16 , 31 , 32 , 34 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] ( Figure 3 ). In particular, if we only consider monoterpenes, the concentration range of seven of them under the canopy of a Scots pine forest was reported in a study [ 44 ] ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations